Associations between age, social reward processing and social anxiety symptoms - Kilford, EJ; Foulkes, L; Blakemore, S-J (Springer, 2023)
Reward processing undergoes marked changes in adolescence, with social interactions representing a powerful source of reward. Reward processing is also an important factor in the development of social anxiety disorder, a condition that most commonly first appears in adolescence. This study investigated the relationship between age, social reward processing and social anxiety in a cross-sectional sample of female participants (N = 80) aged 13–34. Participants performed two versions of a probabilistic reward anticipation task, in which a speeded response could result in different probabilities of receiving either social or monetary rewarding feedback. Participants also completed self-report assessments of social reward value, trait anxiety and social anxiety symptoms. At high reward probabilities, performance on both reward tasks showed a quadratic effect of age, with the fastest responses at around 22–24 years. A similar quadratic effect was found for subjective liking ratings of both reward stimuli, although these were not associated with performance. Social anxiety was not associated with a subjective liking of the rewards but did predict performance on both tasks at all reward probabilities. Age-related variation in reward processing was not accounted for by age-related variation in social anxiety symptoms, suggesting that, while both social anxiety and age were associated with variation in reward processing, their effects were largely independent. Together, these findings provide evidence that social reward processing continues to develop across adolescence and that individual differences in social anxiety should be considered when considering reward sensitivity during this period.